2016
DOI: 10.1111/imm.12681
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ and CD8+ T‐cell immunity to Dengue – lessons for the study of Zika virus

Abstract: SummaryDengue virus (DENV) and Zika virus (ZIKV) are rapidly emerging mosquito-borne flaviviruses that represent a public health concern. Understanding host protective immunity to these viruses is critical for the design of optimal vaccines. Over a decade of research has highlighted a significant contribution of the T-cell response to both protection and/or disease enhancement during DENV infection, the latter being mainly associated with sub-optimal cross-reactive T-cell responses during secondary infections.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 63 publications
1
61
0
Order By: Relevance
“…indicated that, following heterologous DENV infection, memory CD8 + T cells expanded that recognized conserved NS proteins (33). In fact, NS3 and NS5 represent the main targets of the CD8 + T cell response to flaviviruses (34, 35). One study reported more cross-reactive T cell responses to full length NS3 helicase, because of higher sequence homology, than that to the protease region alone (36).…”
Section: Discussionmentioning
confidence: 99%
“…indicated that, following heterologous DENV infection, memory CD8 + T cells expanded that recognized conserved NS proteins (33). In fact, NS3 and NS5 represent the main targets of the CD8 + T cell response to flaviviruses (34, 35). One study reported more cross-reactive T cell responses to full length NS3 helicase, because of higher sequence homology, than that to the protease region alone (36).…”
Section: Discussionmentioning
confidence: 99%
“…ZIKV is a flavivirus most closely related to dengue virus (DENV) (5,6) but also related with Japanese encephalitis virus (JEV), West Nile virus (WNV), and yellow fever virus (YF), all of which are transmitted primarily by mosquitoes (7). Understanding host protective immunity to this virus is critical for the design of optimal vaccines, but little is currently known about the immune responses to ZIKV in humans since infections with ZIKV have not been frequent in the past (8,9). This is in contrast to a substantial wealth of information related to T cell immunity against the closely related DENV (10)(11)(12).…”
mentioning
confidence: 99%
“…The main protein targets of CD4 and CD8 T cell immunity are presently unknown for ZIKV. This dearth of information is a severe knowledge gap, as robust T cell responses may be required for optimal ZIKV vaccine efficacy (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another ongoing unknown is the consequence of sequential infections with Zika and Dengue: is the antigenic relationship one that fosters cross‐reactive protection or pathogenic enhancement of virion uptake? The relationship between T‐cell recognition of Dengue and Zika was recently evaluated by Rivino and Lim . While there is a substantial dataset of Dengue T‐cell recognition, there is much yet to be resolved about Zika adaptive immunity.…”
mentioning
confidence: 99%